Effective strategies for developing school organizational culture by junior high school principals - Aflah, Nurul; Usman, Nasir; Murniati; Bahrun; Hayati, Raudhatul (Indonesian Journal of Educational Development (IJED), 2026)
School organizational culture has a strategic role in character development, work ethic, and the quality of education. However, many junior high schools still face challenges, including low discipline, limited teacher participation, and a weak culture of leadership and collaboration. This study aims to analyze and describe the strategies school principals use to develop an effective school organizational culture at the junior high school level. This study uses a descriptive qualitative design with a case study method at SMP Negeri 1 Teunom. Data were collected through interviews, observations, and documentation of the principal, teachers, and educational staff, then analyzed through a process of reduction, data presentation, and conclusion. The results of the study show three main strategies: (1) strengthening religious and academic literacy culture to shape the religious and intellectual character of the school community; (2) exemplary behavior, communication, and responsibility; and (3) the application of collaborative, transformational, and managerial leadership styles that encourage participation, innovation, and professionalism among teachers. These three strategies create an adaptive, disciplined, and quality-oriented organizational culture. This study contributes to strengthening educational leadership theory and provides practical recommendations for principals on creating a collaborative, character-building work environment.